O redondo, o interior e o exterior : materializações do desejo na escultura monumento "Tocar o Sol", de Quintino Sebastião - Cirillo, Aparecido José (2019)
This article looks at the documents the artist Quintino Sebastião (1940), which refers to the initial image of the public art piece “Touch the Sun”, 2001. We identified, in 148 sketchbooks, some of his thought about his intentions and choices to the project. The image (Round) reveals an artist’s tendency to the women body sensuality, and seems to follow the rounded shape of female breasts. The study focuses on the process of critical and inferential criticism; beyond the phenomenology of the round and the dialectics of outside and inside